Exploration of Casson hybrid nanofluid (Cu−Al2O3/EG) flow over an exponentially heated stretchy sheet with radiation absorption and viscous dissipation: A modified Buongiorno model - S. Baskaran; R. Sowrirajan; S. Eswaramoorthi; K. Loganathan; Balachandra Pattanaik (International Journal of Thermofluids, 2025)
The past few decades have seen a notable rise in research on non-Newtonian fluid models. The Casson fluid serves as a prominent representation of non-Newtonian fluids. The widespread interest can be linked to the valuable applications of these models across different engineering fields and industries. This analysis focused on the flow of a Casson fluid mixed with (Cu) and (Al2O3) nanoparticles in ethylene glycol across a heated porous exponentially stretchy sheet with slip, radiation, viscous dissipation and radiation absorption effects. Employing suitable transformations, the system of governing nonlinear partial differential equations are reformed into ordinary differential equations, which are numerically computed by adopting the bvp4c solver in MATLAB. Tables and figures are used to explore the effects of essential factors on velocity, temperature, and nanofluid concentration distributions and also the skin friction coefficient, the local Nusselt number, and the local Sherwood number. The velocity of the fluid diminutives with an enhanced values of the Casson parameter. The temperature distribution elevates as the Brownian motion and thermophoresis parameters enrich. An escalation in the Lewis number and the Brownian motion parameter promotes a reduction in the nanofluid concentration profile. The mass transference rate is enhanced by the amplification of Brownian motion and thermophoresis parameters.